Celebrating Applied Sciences Reaches 20,000 Articles Milestone: Invited Papers in "Applied Dentistry and Oral Sciences" Section - Melo, Mary Anne (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We are delighted to present this Special Issue to celebrate a remarkable milestone in the journey of Applied Dentistry. With great pleasure, we announce the publication of the journal's 20,000th paper. This remarkable achievement reflects the unwavering commitment and dedication of our esteemed authors, reviewers, and readers who have contributed to the advancement of dental research.Over the years, Applied Dentistry has emerged as a beacon of knowledge, serving as a platform for the dissemination of cutting-edge research and innovative ideas in various domains of dental science. Our journal encompasses a wide range of disciplines, covering everything from dental materials and biomaterials to preventive and therapeutic strategies, from clinical applications to regenerative dentistry.We envision this milestone as a stepping stone toward even greater accomplishments. Through the collaboration and collective efforts of researchers worldwide, we strive to push the boundaries of dental science, explore new frontiers, and improve oral health outcomes for individuals across the globe.In conclusion, we extend our warmest congratulations to all those who have contributed to the publication of the Special Issue celebrating Applied Dentistry's 20,000th paper milestone.